(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This study examines the impact of forward-looking disclosure on financial reporting quality for 26 firms listed on the Damascus Securities Exchange (2021–2024). Reporting quality was measured via discretionary accruals (Modified Jones Model), and forward-looking disclosure levels via content analysis of annual reports. It addresses a gap by testing this relationship in an emerging market. Results indicate a statistically significant effect; however, contrary to positive expectations, higher forward-looking disclosure was associated with increased discretionary accruals, signaling greater earnings management and lower reporting quality. This finding remained robust after controlling for firm size, industry type, and leverage. The result is attributed to weak regulatory frameworks, where forward-looking disclosure may be used opportunistically. The study recommends strengthening internal and external audit and regulatory oversight to ensure the credibility of forward-looking disclosures.